Association between sucrose intake and acute coronary event risk and effect modification by lifestyle factors: Malmö Diet and Cancer Cohort Study. Issue 9 (24th October 2016) - Warfa, K.; Drake, I.; Wallström, P.; Engström, G.; Sonestedt, E.
Abstract: Previous studies have suggested that a high intake of sugar-sweetened beverages is positively associated with the risk of a coronary event. However, a few studies have examined the association between sucrose (the most common extrinsic sugar in Sweden) and incident coronary events. The objective of the present study was to examine the associations between sucrose intake and coronary event risk and to determine whether these associations are specific to certain subgroups of the population (i.e. according to physical activity, obesity status, educational level, alcohol consumption, smoking habits, intake of fat and intake of fruits and vegetables). We performed a prospective analysis on 26 190 individuals (62 % women) free from diabetes and without a history of CVD from the Swedish population-based Malmö Diet and Cancer cohort. Over an average of 17 years of follow-up (457 131 person-years), 2493 incident cases of coronary events were identified. Sucrose intake was obtained from an interview-based diet history method, including 7-d records of prepared meals and cold beverages and a 168-item diet questionnaire covering other foods. Participants who consumed >15 % of their energy intake (E%) from sucrose showed a 37 (95 % CI 13, 66) % increased risk of a coronary event compared with the lowest sucrose consumers (<5 E%) after adjusting for potential confounders. The association was not modified by the selected lifestyle factors. The results indicated that sucrose consumption higher than 15 E% (5 % of this population) is associated with an increased risk of a coronary event.